Prolonged exposure of the HIV-1 gp41 membrane proximal region with L669S substitution - Shen, Xiaoying (National Academy of Sciences, 2010)
The conserved membrane-proximal external region (MPER) of HIV-1 envelope is a target for the rare broadly neutralizing 2F5, Z13, and 4E10 monoclonal antibodies (mAbs). One strategy to elicit such antibodies is to design an immunogen with increased exposure of the 2F5 and 4E10 mAb epitopes. In this study we characterize a single leucine to serine substitution at position 669 (L669S) in the gp41 Env MPER that confers >250-fold more neutralization sensitivity to 2F5 and 4E10 mAbs than does the wild-type gp41 sequence. On synthetic liposomes, increased solvent exposure of MPER tryptophan residues and stable docking of 2F5 and 4E10 mAbs to mutant MPER peptide liposomes indicate more favorable membrane orientation of MPER neutralizing epitopes with L669S substitution. The time during which virus is sensitive to 2F5 mAb-mediated neutralization is approximately 3-fold longer when the mutation is present. These data suggest that a major contribution to the L669S mutant virus phenotype of enhanced susceptibility to MPER mAbs is prolonged exposure of the MPER neutralizing epitope during viral entry.